DETERMINANTS OF YOUNG ACCOUNTANTS ENTREPRENEURIAL INTENTION IN CENTRAL JAVA: A PLANNED BEHAVIOR THEORY APPROACH - Ihda Fadhila Sari; provita wijayanti; Nur Raihana Mohd Sallem (Politeknik Negeri Semarang, 2026)
The purpose of this study is to analyze young accountantpreneurs in Central Java from the perspective of the Theory of Planned Behavior. Purposive sampling using the Slovin formula was employed to determine the sample size. Data were collected through a Google Form distributed online to 100 respondents. This study employed the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach using SmartPLS 4.0 for data analysis. The results indicate that attitude, subjective norm, and knowledge do not have a positive or significant effect on the intention of young accountants to become accountantpreneurs in higher education institutions in Central Java. However, the self-efficacy component has a significant positive effect on accountantpreneurs’ intention among young accountants in Central Java universities.